Geoeconomic aspects of the cooperation between the Republic of Serbia and the People’s Republic of China: situation and perspectives - Božić Miljković, Ivana (Sociološki pregled, 2021)
The subject of this paper is the economic relations between the Republic of Serbia and the People’s Republic of China from the beginning of the century until today. The development of these economic relations and cooperation is based on the long tradition of their good political and diplomatic relations. The relationship of these two countries towards the transition and different strategies in the implementation of this process are determinants of their economic success and the position they have in the global economy. The aspects of the economic cooperation between Serbia and China are analyzed in two categories in which this cooperation is most visible and in which its effects can be precisely expressed quantitatively: the cooperation in the field of foreign trade and in the field of investments. The basic hypothesis is that the economic relations between Serbia and China have been growing rapidly since the beginning of the century and that such a trend will continue in the future at the bilateral level, but also within the program of various cooperation platforms initiated by China and signed by Serbia. China’s position in international institutions enables the protection of Serbia’s territorial integrity, which is another important dimension of their mutual relations.